COMPARATIVE ANALYSIS OF ROMANIAN AND GERMAN NEGOTIATION STYLE BASED ON CULTURAL DIFFERENCES - ANDREA HAMBURG (Annals of the University of Petrosani: Economics)
As a result of intensified international business relations and a unified European space the cultural background of economic agents in the field of international business is getting an increasing importance and leaves to a certain extent its marks on business behaviour of these individuals. Thus from the sixties of the past century onwards the problem of cultural differences and their influence upon professional relations lie in the centre of attention of several researchers like E.T. Hall, Geert Hofstede and others. In business negotiations one may observe a double conditioning of people’s negotiation style, at one hand it is the result of individual characteristics like personality, education, experience, personal charisma, but on the other hand there is a strong impact of collective factors, too such as the mental programming of each nation known under the name of culture. In the following study we undertake a Comparative/contrastive analysis of German and Romanian – culturally conditioned – negotiation style hoping to avoid at the same time to fall into the trap of stereotypy.